Empowering Muhammadiyah Cadres for Da'wah-Based Digital Transformation in Multicultural Communities - Sinduwiatmo, Kukuh; Wardana, Mahardika Darmawan Kusuma; Widyastuti, Widyastuti (Indonesian Journal of Cultural and Community Development, 2025)
This research aims to empower Muhammadiyah cadres in developing digital skills and da'wah communication abilities to support the digital transformation of agricultural products in the Bromo Tengger multicultural community. A qualitative approach with participatory methods was used in this research. Data collection techniques included in-depth interviews, participatory observation, and documentation of activities, with thematic analysis to identify key patterns. The empowerment of Muhammadiyah cadres succeeded in improving digital skills, ability in marketing agricultural products through digital platforms, as well as strengthening the value of da'wah in communication strategies. The cadres were able to build a wider marketing network and integrate Islamic values in multicultural interactions. This research offers an empowerment model based on communication education and digital da'wah that is contextual to multicultural communities, and integrates digital transformation with religious values. The practical implications of this research encourage the development of community-based empowerment programs that prioritize digital literacy and contextual da'wah approaches to support local product marketing in the digital era. Limitations lie in the short implementation time and limited sample representation. Further research is recommended to expand the implementation of this model in other multicultural communities.